THE USE OF MODELING FOR INTERPRETATION OF OBSERVED LIGHT CURVES OF SATELLITES - Melikyants, S.; Shakun, L.; Koshkin, N.; Dragomiretsky, V.; Strakhova, S. (Одеські астрономічні публікації, 2017)
In this work the opportunity of interpretation of light curves of artificial satellite is investigated by using of theoretical light curves of its model. For this purpose the programming language Max Script and the applied program for computer’s three-dimensional drawing for visualization of the generated model is used. The opportunities of the programming language and effectiveness of this application for optic-geometrical modeling of satellite are tested. This allows to generate satellite models, allows to set optical parameters of surfaces, to simulate adequately geometrical conditions of movement and supervision of the model. The theoretical integrated light curves of really supervised satellites were calculated, particularly of the cosmic apparatus Sich-1M. The comparison of supervised and theoretical light curves allows to make a conclusion about the mode of movement of satellite around its center of weight, and to make the remote sensing of the its state and behavior. The computing information on the model’s light reflection in several color bands can be used, in addition, for interpretation of multi-color observations of satellites.